(untitled) (Bangladesh Journal of Zoology, 2025)
The mitochondrial 16S ribosomal RNA (16S rRNA) gene has emerged as a reliable alternative to morphological identification for identifying damselflies. In this study, an average of 478 bp 16S rRNA sequences was generated from four damselfly species. A GenBank BLAST search found that three of the four damselfly species had sequence similarity ranging from 98% to 99%. However, the only species that did not show a significant match to Genbank was identified morphologically as Aristocypha quadrimaculata. The sequences of A. quadrimaculata and three other matching species were then submitted to Genbank, where they were assigned accession numbers PP464226 (Pseudocopera ciliata), PP464231 (Euphaea ochracea), PP464251 (A. quadrimaculata), and PP464253 (Pseudagrion rubriceps). In the present study, A. quadrimaculata sequences were the first submission to the NCBI GenBank database. After analysis of the four sequences, the interspecific genetic divergence between the four species ranged from 0.203 to 0.977%. Later, a phylogenetic tree was constructed and the results showed that the four damselfly species came from a common ancestor. The phylogenetic tree presented a single major group where P. rubriceps, P. ciliata and A. quadrimaculata resided. On the other hand, E. ochracea exists in a remote area where this species has a longer branch, indicating significant genetic divergence from the other three damselfly species. Additionally, a TCS haplotype network of 16S rRNA gene sequences was constructed. Among the four damselfly species, E. ochracea has the largest number of mutation sites (193 sites). This reveals that E. ochracea has become genetically distant from the other three damselfly species. Finally, 16S rRNA gene-based identification is rapid and accurate, and barcodes can validate unknown species, monitor biodiversity, and determine evolutionary relationships. Bangladesh J. Zool. 52(3): 311-322, 2024